Improving optical properties of white light-emitting diodes using triple-layer remote structure - Thanh Binh Ly; Phan Xuan Le (Institute of Advanced Engineering and Science, 2022)
Inrecent efforts to improve the performance ofwhite light-emitting diode (WLEDs), researchers have focused on angular color uniformity (ACU), an effective index for evaluating the light quality of WLEDs. Inthis article, we also aim for the WLED development by applying three phosphor layers in the remote phosphor structure. The dual-layer phosphor (DLP) remote structure is also included in the research for comparison with the triple-layer phosphor (TLP) in terms of their impacts on the lighting quality of WLEDs. To ensure the diversity and applicability in different scenarios, performancesof multi-layer phosphor structures in WLED devices with average correlatedcolor temperatures (ACCTs) from 5600 K to 8500K are measured. The experimental results have proved that both TLP and DLP structures are suitable to enhance WLEDs’ performance as each structure excels at specific qualities. In particular, at all ACCTs, the DLP structure is getting better in improvingthe color rendering index (CRI), while the TLP is more advantageous to color quality scale (CQS) and light output. The TLP also presents a lower color deviation than the DLP does, which leads to a better color uniformity in WLEDs at all ACCTs.